Patulous Eustachian tube (PET), a practical overview - Manohar Bance; James R. Tysome; Matthew E. Smith (World Journal of Otorhinolaryngology-Head and Neck Surgery, 2019)
Symptoms of patulous Eustachian tube (ET), particularly autophony, can overlap with other conditions, and can arise from a variety of causes. We review the pathophysiology of “speech hyper-resonance syndromes”, and possible mechanisms, including resonances in the tympanic membrane, Eustachian tube and nasopharynx. Treatment can be directed at the eardrum or the ET depending on site of pathology. We review typical presentations, examination findings, and useful clinical tests to distinguish PET from other disorders, and our philosophy of management. Keywords: Patulous Eustachian tube, Autophony, Cartilage typmpanoplasty, Eustachian tube function testing, Sonotubometry